Whom Do They Serve? A National Examination of Veterans Treatment Court Participants and Their Challenges - Baldwin, Julie Marie (Criminal justice policy review, 2017)
The veterans treatment court (VTC) is a recently developed specialized court that targets the growing population of veterans in contact with the criminal justice system. Using data collected from the first national survey of VTCs in 2012, this study explores who VTC participants are by creating a descriptive portrait of their personal and military characteristics and the legal, extralegal, and programmatic challenges they face. This study also examines the perceived relationships between military service and legal and extralegal issues. This research produces the first early illustration of VTC participants on a national level, finding similarity and variability across VTCs, in comparison with the national veteran population, and between servicemen and servicewomen on a variety of factors. Furthermore, this study identifies recent changes in the VTC participant population. Recommendations for VTC programs and for research on justice-involved veterans and active-duty personnel are provided in light of the fluid VTC population.